2007
DOI: 10.1038/sj.bjp.0707360
|View full text |Cite
|
Sign up to set email alerts
|

A ginseng‐derived oestrogen receptor β (ERβ) agonist, Rb1 ginsenoside, attenuates capillary morphogenesis

Abstract: A ginseng-derived oestrogen receptor b (ERb) agonist, Rb1 ginsenoside, attenuates capillary morphogenesis A PapapetropoulosLaboratory of Molecular Pharmacology, Department of Pharmacy, University of Patras, Patras, GreeceGinseng extracts contain a variety of active ingredients and have been shown to promote or inhibit angiogenesis, depending on the presence of different ginsenosides that exert opposing effects on blood vessel growth. Leung et al. in this issue of the British Journal of Pharmacology report that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…In addition, ginsenoside-Re has nongenomic effects of in endothelial cells via the glucocorticoid receptor [58]. Ginsenoside Rb 1 may attenuate capillary morphogenesis by the action of oestrogen receptor beta agonist [59] and induces the signaling pathway of NO production in human aortic endothelial cells [60]. Ginsenoside Rg 1 and Re isolated from P. ginseng are stable angiogenic agents [61].…”
Section: Efficacy Of Regulating Vascular Endothelial Cellsmentioning
confidence: 99%
“…In addition, ginsenoside-Re has nongenomic effects of in endothelial cells via the glucocorticoid receptor [58]. Ginsenoside Rb 1 may attenuate capillary morphogenesis by the action of oestrogen receptor beta agonist [59] and induces the signaling pathway of NO production in human aortic endothelial cells [60]. Ginsenoside Rg 1 and Re isolated from P. ginseng are stable angiogenic agents [61].…”
Section: Efficacy Of Regulating Vascular Endothelial Cellsmentioning
confidence: 99%
“…For example, ginsenoside Rb1 can potently inhibit angiogenesis in vivo and in vitro which is a crucial step in tumor growth and metastasis [71]. Its mechanism was that Rb1 suppressed the formation of endothelial tube-like structures through modulation of pigment epithelium-derived factor via estrogen receptor- β (ER β ) [71, 72]. Rg1 was found to be a phytoestrogen that exerted estrogen-like activity even without direct interaction with oestrogen receptor (ER) in human breast cancer (MCF-7) cells via phosphorylation of AF-1 domain in the absence of receptor binding [73].…”
Section: Interaction With Potential Receptorsmentioning
confidence: 99%
“…Rg1 was found to be a phytoestrogen that exerted estrogen-like activity even without direct interaction with oestrogen receptor (ER) in human breast cancer (MCF-7) cells via phosphorylation of AF-1 domain in the absence of receptor binding [73]. These actions of ginsenosides may have potential value in anti-cancer and anti-angiogenesis therapy although some discrepancy still remained in these studies [72]. …”
Section: Interaction With Potential Receptorsmentioning
confidence: 99%
“…We have also demonstrated that 20(S)-Ginsenoside Rg3 prevents endothelial cell apoptosis via inhibition of a mitochondrial caspase pathway [36]. Interestingly, Leung et al have recently reported that Rb1 regulates capillary morphogenesis through binding and activation of the oestrogen β receptor in ECs [35,37]. These results suggest that individual ginsenosides have different functional roles in the vasculature and have specific agonistic or antagonistic actions depending on EC receptor context and on the side chain moieties attached to their unique sterol backbone.…”
Section: Discussionmentioning
confidence: 99%